Increasing serum albumin in patients with hypoalbuminemia does not inhibit serum angiotensin-converting enzyme activity: Serum Albumin Increase and Serum ACE Activity in Hypoalbuminemic Patients - Rezaei, Mitra; Ghafghazi, Shiva; Kazemzadeh Hemmesi, Maryam; Miri, Mirmohamad; Zarei, Malek; Ziai, Seyed Ali (Student Research in Translational Medicine, 2023)
Introduction: Angiotensin-converting enzyme (ACE) plays a pivotal role in the production of angiotensin II and the inactivation of bradykinin. Recent studies have suggested that human serum albumin may possess ACE-inhibitory properties, serving as a potential endogenous ACE inhibitor that primarily affects serum ACE levels. Interestingly, the infusion of albumin in the postoperative phase of cardiac surgery has been associated with the development of hypotension. Methods: This study aimed to assess serum ACE activity in 27 hypoalbuminemia patients admitted to the ICU before and after a protein-rich diet was administered to raise their serum albumin levels. Serum ACE activity was quantified using raas(HPLC), measuring the formation of hippuric acid, a product generated during the incubation of serum with Hip-His-Leu, a substrate, at 37°C for 30 minutes. Results: In vitro experiments demonstrated that the addition of albumin to human sera led to a significant reduction in ACE activity compared to control groups (P < 0.0001). This reduction was consistent across all serum samples. Specifically, the maximum velocity (Vmax) of ACE activity significantly decreased from 14.90 U/L in the control group to 3.210 U/L in the albumin-added group (P = 0.0262). Notably, there was no significant change in the Michaelis constant (Km) between the control group (0.5263 mM) and the albumin group (0.2742 mM) (P = 0.6763), indicating a non-competitive inhibitory effect of albumin on ACE activity. Interestingly, in this study, elevating serum albumin levels in hypoalbuminemia patients following a protein-rich diet resulted in both ACE inhibition and a slight increase in activity (P = 0.0201). This increase correlated mildly with serum albumin levels across all samples. Conclusions: In conclusion, contrary to in vitro findings, raising serum albumin levels in hypoalbuminemia patients did not further inhibit serum ACE activity.